2019
DOI: 10.14295/cs.v9i4.2529
|View full text |Cite
|
Sign up to set email alerts
|

Potential predation and fecundity of Amblyseius aerialis fed two-spotted spider mite

Abstract: The mites of the Phytoseiidae family stand out for the biological control of pest mites. The species Amblyseius aerialis (Muma, 1955) is a generalist mite, which can contribute to the natural regulation of pest mites. The objective of this study was to evaluate the potential for predation and fecundity of A. aerialis on the different phases of Tetranychus urticae (Koch, 1836) (Acari: Tetranychidae). A female of A. aerialis was confined on dish (3.0 cm in diameter) of jack bean leaves, Canavalia ensiformis (L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Sternal shield smooth, lightly sclerotized with three pairs of setae (ST1, ST2, ST3), two pairs of poroids (pst1 and pst2). Distance (ST1-ST3) 57 (53)(54)(55)(56)(57)(58)(59), width (ST2-ST2) 66 (63)(64)(65)(66)(67)(68)(69). Metasternal setae ST4 and a pair of pores (pst3) on metasternal shields.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Sternal shield smooth, lightly sclerotized with three pairs of setae (ST1, ST2, ST3), two pairs of poroids (pst1 and pst2). Distance (ST1-ST3) 57 (53)(54)(55)(56)(57)(58)(59), width (ST2-ST2) 66 (63)(64)(65)(66)(67)(68)(69). Metasternal setae ST4 and a pair of pores (pst3) on metasternal shields.…”
Section: Plos Onementioning
confidence: 99%
“…It was first collected feeding on six-spotted spider mite, Eotetranychus sexmaculatus, and has since been found in citrus orchards from Guadeloupe, Dominican Republic, Florida, and Brazil [51,54,61,62]. Studies showed that it can feed and reproduce on T. urticae [63,64]. The oviposition rate of A. aerialis was shown to be high on Raoiella indica Hirst (Acari: Tenuipalpidae) and cattail pollen, Typha dominguensis [62,64], as well as on African oil palm pollen (Elaeis guineensis), and coconut pollen (Cocos nucifera) (both Arecaceae) [62], and low on Calacarus heveae Feres (Acari: Eriophyidae) and T. urticae [64].…”
Section: Implications For Biological Controlmentioning
confidence: 99%